Penulisan Abstrak Bahasa Inggris - Nurdin Noni; Maemuna Muhayyang; Sahril Sahril (DEDIKASI, 2020)
This partnership program aims to provide knowledge and skills of writing an English abstract for English Teacher Association, Somba Opu district, Gowa used to express their ideas in a brief, concise, conclusive and informative manner to produce some scientific works. It is expected that it can develop skills, attitudes and a writing culture as a medium for sharing concrete thoughts, both through printed and non-printed media. This program is packaged in the form of training which consists of several activities , namely (1) presentation of material  about the concept of basic writing of an abstract by utilizing the online facilities of information and technology  in the current situation of a pandemic covid 19, namely Zoom, Google Meet, and Watch Application, (2)  individual assignment to write an abstract , (3) abstract presentation , and (4 ) revision of abstract  in terms of choice of diction or grammatical mistakes given during the presentation session. The methods used in this training are quite varied, namely lectures, discussions/presentations, and individual consultations to the team.  The result of this program showed that (1) the participants gained a good understanding about the concepts and writing organization for English abstract, and (2) there were 85% of them were able to make up a well-organized abstract. It takes into account that this program has a positive impact toward their participant knowledge and skill of writing an English abstract.